Fabrication and Characterization of Supported Porous Au Nanoparticles (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Porous plasmonic nanoparticles offer unique advantages for sensing and catalysis due to their high surface-to-volume ratio and localized electromagnetic field enhancements at nanoscale pores, or “hotspots.” However, current fabrication techniques, which are based on colloidal synthesis, face challenges in achieving precise control over particle size, shape, and porosity. Here, we present a robust nanofabrication method to produce supported arrays of porous Au nanoparticles with excellent dimensional and compositional control. By combining lithographically patterned AuAg alloy nanoparticles and selective dealloying via nitric acid, we achieve particle porosity without compromising particle morphology. Specifically, the method allows fabrication of supported porous nanoparticles with tunable dimension and porosity. Our approach demonstrates precise control of nanoparticle porosity by varying the initial Ag content in the alloy. Optical characterization reveals a blueshift in the extinction peak with increasing porosity, attributed to the reduced effective refractive index from intraparticle voids. Notably, a tunable shift of up to 100 nm in the plasmonic peak is observed, demonstrating the potential for fine-tuning optical properties. This study highlights the versatility of the proposed method in fabricating well-defined porous plasmonic nanoparticles and their ability to modulate optical properties through porosity control. These findings not only expand the toolkit for designing advanced plasmonic materials but also open pathways for applications in plasmon-mediated sensing, catalysis, and photonic devices.